The essential role of pharmacists facilitating vaccination in older adults: the case of Herpes Zoster - Casey R. Tak; Macary Weck Marciniak; Amanda Savage; Sachiko Ozawa (Human Vaccines & Immunotherapeutics, 2020)
Older adults share a disproportionately high burden of vaccine-preventable diseases. Despite recommendations from national and international health organizations, vaccination rates among older patients remain suboptimal, suggesting poor access and barriers to vaccination. Pharmacists are uniquely positioned to assist patients in overcoming many of these barriers. In this commentary, we describe some of the common barriers to vaccination that older adults encounter and the role pharmacists have in overcoming these barriers, in the US and abroad. We provide a case study of pharmacists’ impact in supporting herpes zoster vaccination. We also identify areas of opportunities to promote further pharmacist involvement in vaccination efforts.